1995
DOI: 10.2105/ajph.85.8_pt_1.1149
|View full text |Cite
|
Sign up to set email alerts
|

Retaining cocaine-abusing women in a therapeutic community: the effect of a child live-in program.

Abstract: A clinical trial examined whether retention of cocaine-abusing women in a therapeutic community can be improved by permitting their children to live with them during treatment. Fifty-three women were randomly assigned to either the standard community condition (n = 22), in which children were placed with the best available caretaker, or the demonstration condition (n = 31), in which one or two of the children lived with their mother in the community. Survival analysis distributions indicated that demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 14 publications
2
54
0
2
Order By: Relevance
“…This project found that the women were significantly more likely to complete the women-focused intensive day program than those who attended a residential program for women and their children or a traditional residential program (Roberts and Nishimoto, 1996). Within residential programs, however, policies allowing children to accompany their mothers in treatment have been demonstrated to have a positive impact on treatment retention (Hughes et al, 1995;Szuster et al, 1996). A randomized trial of female cocaine-abusing patients assigned women to the experimental condition, in which one or two of the children joined the woman in residential treatment, or the control condition of placing the children with a caregiver outside the therapeutic community (Hughes et al, 1995).…”
Section: Program-related Characteristics Associated With Treatment Rementioning
confidence: 99%
See 3 more Smart Citations
“…This project found that the women were significantly more likely to complete the women-focused intensive day program than those who attended a residential program for women and their children or a traditional residential program (Roberts and Nishimoto, 1996). Within residential programs, however, policies allowing children to accompany their mothers in treatment have been demonstrated to have a positive impact on treatment retention (Hughes et al, 1995;Szuster et al, 1996). A randomized trial of female cocaine-abusing patients assigned women to the experimental condition, in which one or two of the children joined the woman in residential treatment, or the control condition of placing the children with a caregiver outside the therapeutic community (Hughes et al, 1995).…”
Section: Program-related Characteristics Associated With Treatment Rementioning
confidence: 99%
“…While mixed-gender samples allow for examination of gender-specific predictors of retention, a number of studies have examined predictors of retention among women-only samples (Brown et al, 1995;Davis, 1994;Hughes et al, 1995;Huselid et al, 1999;Haller and Miles, 2004;Kelly et al, 2001;Knight et al, 1999;Loneck et al, 1997;Stahler et al, 2005;Szuster et al, 1996). Research using women-only samples has found associations between certain patient characteristics (e.g., psychological function, personal stability and social support, levels of anger, treatment beliefs, and referral source) and rates of retention and completion.…”
Section: Individual Characteristics Associated With Treatment Retentimentioning
confidence: 99%
See 2 more Smart Citations
“…The study used a nondirectional hypothesis since this was an exploratory study. While most studies indicate that women who have their children with them in treatment were likely to complete treatment (Hughes, Coletti, Neri, Urmann, 1995;Knight, Logan, & Simpson, 2001;Nishimoto & Roberts, 2001;Stahl, Sicillian, & Anthony, 1995;Szuster, Rich, Chung, & Bisconer; Strantz, & Welch, 1995), at least one study suggests that women who had custody of their children and who had significant child care responsibilities were less likely to complete treatment (Knight, Logan, & Simpson, 1999). Further, much of the relevant TANF research is descriptive, and there is little research that assesses the impact of receiving TANF cash benefits on women's drug treatment outcomes (Gutman, Ketterling & McLellan 2003;Keesee & Williams, 1997;Montoya, Atkinson & Struse, 2001).…”
mentioning
confidence: 99%